Kondisi Eksisting Ketahanan Pangan Rumah Tangga Petani: Peran Gender dan Pemberdayaan Istri Petani - Winarti, Lili; Maswadi, Maswadi; Permadi, Rokhman; Juliyanto, Leo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Household food security among pineapple farmers is one of the critical issues in the development of the agribusiness sector, particularly in East Kotawaringin Regency, Central Kalimantan. Although pineapples are one of the region's leading commodities with a production of 336.4 tons in 2022, their contribution to improving farmer welfare remains suboptimal. This study aims to examine the existing condition of household food security among farmers, the role of gender, and the empowerment of farmers' wives in East Kotawaringin Regency. The research was conducted in five districts with the highest pineapple production using the purposive sampling method, with 296 respondents determined using the Yamane Formula. Data analysis was carried out descriptively to identify socio-economic characteristics, levels of food security, gender inclusion, and the empowerment of farmers' wives. The results show that 71.62% of pineapple farmer households fall under the food-secure category, while 23.99% are slightly food insecure, and 4.39% are moderately food insecure. The leadership dimension contributes the most to the empowerment of farmers' wives (30.97%), followed by dimensions of production, income, resources, and time. The main challenges include low education levels, limited access to agricultural extension services, and gender-based barriers. This study emphasizes the importance of inclusive policies for women's empowerment in pineapple agribusiness to enhance food security and the sustainable welfare of farmer households.